Perancangan User Interface (UI) dan User Experience (UX) SIM Klinik Kodefikasi Klinis - Aini, Nita Dwi Nur; Maulana, Moh (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2025)
Medical record officers at Clinic X experience difficulties in determining disease and procedure codes because coding is performed manually, which often results in claim delays due to codes that are insufficiently specific and do not comply with BPJS regulations. Therefore, this study aims to design a UI/UX for the clinical coding module of the Clinic Information System (CIS) at Clinic X, Malang Regency, to ensure faster and more accurate code generation. This study employed a Research and Development (R&D) approach using Figma, involving three medical record officers as informants. The results indicate that the UI/UX design of the clinical coding module consists of five pages: a login page, a coding dashboard page, a coding page, a coding edit page, and a coding report page. The UI/UX interface design covers navigation, page titles, language clarity, icon consistency, colour schemes, visual appearance, layout, font type and size, and overall page structure, all of which were found to be appropriate. The CIS not only functions effectively from a technical perspective but also enhances the comfort and efficiency of healthcare personnel in managing medical data and services.